If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3x = 9x + 6 Combine like terms: 4x + 3x = 7x 7x = 9x + 6 Reorder the terms: 7x = 6 + 9x Solving 7x = 6 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 7x + -9x = 6 + 9x + -9x Combine like terms: 7x + -9x = -2x -2x = 6 + 9x + -9x Combine like terms: 9x + -9x = 0 -2x = 6 + 0 -2x = 6 Divide each side by '-2'. x = -3 Simplifying x = -3
| z^2+(4-3i)z+1-5i=0 | | 96t-9.8t^2=h | | 2c^3+4c^2-6c=0 | | 7x^2+23x+18=0 | | 4x^2+6x-6x=0 | | 12-4v=(3-6v) | | 6x+3(x-4)=7(x-3) | | (6-2c)3c-3=27 | | d^2+11d+18= | | -2y+7=4y-5 | | 20-(x+8)=8x-6 | | (5+x)(5+x)= | | 4w-28+11w+13=180 | | -7(1-x)+15=3(x+8) | | g(x)=x-4 | | -207=-9(-7n+2) | | -2y-16x=14 | | 31x=8x+69 | | 5(8-2)-8(8)=-34 | | 7-(2x-5)=9 | | 65+(10n+6n)=120 | | n^2-2n-63= | | 2+8/c=-10 | | x^2-97x=0 | | 3(-4+-2x+x^2)=0 | | 16=-4x+28 | | 10y+3y-3=24y+30 | | 4n+3(2n-4)=n | | 4m+2(m+1)=23 | | 4-5p=-31 | | -2+18=-x-9 | | 3+2x=3x-4 |